Implications for the study of wide area networks and paintings in their steps fractals (2014)
ABSTRACT: This manual has general information about WAN nets just as subnetting exercises and this nets configuration. All the information been in this manual was develop during the 2013-1 period in this sixth semester of the Engineer in Computer systems university course whit the professor support of the Dr. Felipe A. Gonzalez Gonzalez and every his knowledge's contribution. The principal objectives in this manual is reinforce the basics knowledge's of wide area net just as strengthen the practice of the subnetting exercise and made the configuration process and the carried activities during the semester where the chair has done.